LGG-46. TRAMETINIB THERAPY IN PEDIATRIC PATIENTS WITH LOW-GRADE GLIOMAS (LGG) WITH BRAF GENE FUSION; A DISEASE-SPECIFIC COHORT IN THE FIRST PEDIATRIC TESTING OF TRAMETINIB. Issue 2 (22nd June 2018) - Bouffet, Eric; Kieran, Mark; Hargrave, Darren; Roberts, Stephen; Aerts, Isabelle; Broniscer, Alberto; Geoerger, Birgit; Dasgupta, Kohinoor; Tseng, Lillian; Russo, Mark; Mookerjee, Bijoyesh; Moertel, Christopher
Abstract: BACKGROUND: LGG is the most prevalent childhood brain tumor. BRAF fusions drive constitutive activation of BRAF and tumorigenesis. We report results of trametinib, a MEK1/2 inhibitor, in pediatric patients with LGG with BRAF fusion. METHODS: This phase 1/2 trial (NCT02124772) enrolled pediatric patients (≤18 y) with refractory/recurrent tumors. We report results from interim analysis of pediatric patients with LGG harboring BRAF fusion. Trametinib was dosed at 4 dose levels in part A (0.0125, 0.025, 0.04, and 0.032 mg/kg/d) and at 0.025 mg/kg/day in the expansion cohort. Tumor assessments were performed every 8 weeks by MRI, including T2-FLAIR sequences, using RANO criteria. RESULTS: Twenty-three patients were enrolled across cohorts. Median age of patients was 8 y (range, 2-18) and 13 of 23 were male. At data cutoff, 15 patients were ongoing. One patient discontinued with progressive disease (PD) at 35 weeks, 4 due to adverse events (AEs), 2 per investigator discretion, and 1 per consent withdrawal. The most common treatment-related AEs were diarrhea (14), rash (13), paronychia (9), and maculopapular rash (8). There were no deaths on study. Confirmed partial responses were observed in 3 patients by investigator and 1 patient by independent review. No patients had best response of PD. All responses were ongoing at the data cutoff (all >1 y), and 12 patients had ongoing stable disease (49-121 weeks). CONCLUSION: In pediatric patients with pretreated LGG and BRAF fusion, trametinib was well tolerated, with 1 independently confirmed RANO response, and most patients were without PD >1 y.